African American history in New Mexico : portraits from five hundred years - Glasrud, Bruce A. (University of New Mexico Press, 2013)
Most people think of George McJunkin or the Buffalo Soldiers when they think about African American history in New Mexico, but the state's Black history is richer and more complex and continues to this day. This collection is aimed at providing an overview of the dynamic presence of African Americans throughout the state and its history.--adapted from description provided by publisher.